The relationship between pro-environmental behavior, subjective well-being, and environmental impact: a meta-analysis - Krumm, Laura; Justus Liebig University Giessen (My University, 2024)
A substantial change towards more pro-environmental behavior (PEB) is essential to reach the required reduction in greenhouse gas emissions and mitigate climate change. These behavior changes will have consequences on people’s daily lives and thus might affect their well-being. Previous research generally finds positive correlations between PEB and well-being. This meta-analysis explores whether the relationship between PEB and well-being depends on the environmental impact of the performed PEB. Overall, the paper finds a small but significant positive relation between PEB and well-being. When accounting for the environmental impact of the PEB, however, the positive relationship only remains for low-impact PEB. The meta-analysis does not provide any evidence that engaging in high-impact PEB relates to well-being. Consequently, these findings demonstrate that there is more ambiguity in the relationship between PEB and well-being than previously described in the literature and that the environmental impact of PEB matters when evaluating its relationship with well-being. These findings have important implications for policy-making trying to facilitate mitigation efforts that ultimately aim to balance the well-being of the current and future generations.
Keywords: ddc:640; ddc:360